Haemodynamic Studies with Peruvoside in Human Congestive Heart Failure. Issue 5725 (26th September 1970) - Bhatia, M. L.; Manchanda, S. C.; Roy, Sujoy B.
Abstract : The immediate haemodynamic effects of peruvoside, a cardiac glycoside obtained from the Indian plant Thevetia neriifolia Juss, were studied in six patients with congestive heart failure. The drug was found to have an immediate and powerful positive inotropic and negative chronotropic effect, like ouabain, on the failing human heart. Oral peruvoside was also effective in the treatment of congestive heart failure when used on a short-term as well as a long-term basis. It therefore seems that peruvoside is a useful cardiac glycoside in the management of congestive heart failure in man as a quick-acting intravenous preparation. It is equally effective when used orally.